ANALISIS YURIDIS PEMBATALAN SERTIFIKAT GANDA PADA KANTOR PERTANAHAN KOTA MEDAN (STUDI PUTUSAN MAHKAMAH AGUNG REPUBLIK INDONESIA NOMOR 381 K/TUN/2017) - JUSRIONO PARULIAN SIREGAR (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Muhamamd Yamin2. Saidin3. T. Keizerina Devi A Problems regarding double certificates are frequently found. The owner usually report it to Administrative Court to obtain justice. It spporoaches the problems by analyzing the ruling of the Supreme Court of the Republic of Indonesia No. 381/k/tun/2017. It is also supported by outcome from interview with the Land Agency of Medan, section v public case. The results of the research discovers that practically, the freehold title certificate registrateion has been regulated and issued in accordance with the regulation, yet the ruling of the administrative court annuls one of the certificate that has to be done by the land office of Medan. It is suggested that the land office of Medan correct the bookkeeping system of certificate issuance and other steps required to issue a certificate, so that the society will trust and feel secure to register their land and that there will be not any double certificates.Keywords: Double Certificate, Annulment of Double Certificate I.